Characterization of the Intergenic Spacer rDNAs of Two Pig Nodule Worms, Oesophagostomum dentatum and O. quadrispinulatum - Rui-Qing Lin; Li Shu; Guang-Hui Zhao; Tian Cheng; Shang-Shu Zou; Yuan Zhang; Ya-Biao Weng (The Scientific World Journal)
The characteristics of the intergenic spacer rDNAs (IGS rDNAs) of Oesophagostomum dentatum and O. quadrispinulatum isolated from pigs in different geographical locations in Mainland China were determined, and the phylogenetic relationships of the two species were reconstructed using the IGS rDNA sequences. The organization of the IGS rDNA sequences was similar to their organization in other eukaryotes. The 28S-18S IGS rDNA sequences of both O. dentatum and O. quadrispinulatum were found to have variable lengths, that is, 759–762 bp and 937–1128 bp, respectively. All of the sequences contained direct repeats and inverted repeats. The length polymorphisms were related to the different numbers and organization of repetitive elements. Different types and numbers of repeats were found between the two pig nodule species, and two IGS structures were found within O. quadrispinulatum. Phylogenetic analysis showed that all O. dentatum isolates were clustered into one clade, but O. quadrispinulatum isolates from different origins were grouped into two distinct clusters. These results suggested independent species and the existence of genotypes or subspecies within pig nodule worms. Different types and numbers of repeats and IGS rDNA structures could serve as potential markers for differentiating these two species of pig nodule worms.